First record of the invasive gecko, Lepidodactylus lugubris Dumeril & Bibron, 1836 in mainland Chile (Squamata, Gekkonidae) - Urra, Félix A.; Zúñiga, Alejandro; Miranda Calle, Alejandro Bruno.; Melero, Nel. (Österreichische Gesellschaft für Herpetologie, 2020)
In Chile, the presence of Mourning Gecko, Lepidodactylus lugubris Duméril & Bibron, 1836 has been recognized for Easter Island (Rapa Nui) from late 19th century. Here, we report the first observation of a juvenile specimen of L. lugubris in an urban zone of Santiago, Región Metropolitana, mainland Chile, representing the southernmost non-insular record in America for this invasive species. Moreover, an updated distributional map of L. lugubris for South America and the Antilles is provided.
Keywords: Lizards.; Mourning Gecko.; New records, non-native species.